Presentation: the current narrative of Arequipa - Valle Rondón, Fernando (2010)
This issue has been conceived with the purpose of publicizing recent historiographical works on Arequipa, a clearly significant region in Peru that in recent years has to its credit the innovative and fruitful intellectual production of several young researchers. The articles published here are the result of the constant, silent and patient work of a new generation that, despite the difficulties of research in this country, has been developing efforts to address new issues from various approaches and fields such as Cultural History , economic-social, legal and historiography. The composition of this selection of articles also responds to the express purpose of presenting works on regional history, dedicating an issue to one or more particular regions from time to time.